2013
DOI: 10.1039/c3ra42319k
|View full text |Cite
|
Sign up to set email alerts
|

Graphene–MoO2 hierarchical nanoarchitectures: in situ reduction synthesis and high rate cycling performance as lithium-ion battery anodes

Abstract: Hierarchical nanoarchitectures constructed by MoO 2 nanocrystalfunctionalized graphene were fabricated through an in situ reduction process. As an anode, even at a 10C (0.1 h per half cycle) charging-discharging rate, the reversible capacity is much higher than the theoretical capacity of graphite. Thus, rapid charging-discharging of the anodes is achieved by the nanoarchitectures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…MoO2 has been synthesized using various techniques [469]: template method [455,[470][471][472][473], hydrothermal method [467,[474][475][476][477][478], reduction of MoO3 [479][480][481], soft chemistry route [464,465,482], spray pyrolysis [483][484][485], carbothermal reaction [486], ion-exchange route [487], and so on. Traditionally, molybdenum dioxide is prepared by reducing MoO3 with hydrogen at high temperature and the product grows as micrometer size [479,480].…”
Section: Lithium Insertionmentioning
confidence: 99%
See 1 more Smart Citation
“…MoO2 has been synthesized using various techniques [469]: template method [455,[470][471][472][473], hydrothermal method [467,[474][475][476][477][478], reduction of MoO3 [479][480][481], soft chemistry route [464,465,482], spray pyrolysis [483][484][485], carbothermal reaction [486], ion-exchange route [487], and so on. Traditionally, molybdenum dioxide is prepared by reducing MoO3 with hydrogen at high temperature and the product grows as micrometer size [479,480].…”
Section: Lithium Insertionmentioning
confidence: 99%
“…Significantly, the composite can also deliver a reversible capacity of as high as1009 mAh g −1 after 60 charge/discharge cycles. Chen et al [481] reported the electrochemical properties of hierarchical nanocomposites including MoO2 nanocrystal-functionalized graphene synthesized by in-situ reduction process. The discharge capacity is still up to 997 mAh g −1 after 50 cycles and 370 mAh g −1 after 200 cycles at 10C rate.…”
Section: Moo2/graphene Compositesmentioning
confidence: 99%
“…In order to overcome this problem, MoO 2 with different morphology have been synthesized, such as MoO 2 nanospheres, [13] ordered mesoporous MoO 2 , [3] tremella-like MoO 2 , [11] MoO 2 nanoparticles, [12] MoO 2 nanofibers [14] and ultrafine MoO 2 nanosheets. [15] Besides, carbonaceous materials such as amorphous carbon, [13,16] carbon nanotubes (CNT) [17,18] and graphene [19][20][21] have been used to incorporate with MoO 2 . Among these carbon materials, the amorhous carbon with good conductivity can improve the conductivity of MoO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24] However, MoO 2 has poor capacity retention due to its signicant volume changes during lithiation and delithiation process. 25,26 A common strategy to reduce the volume change is to incorporate MoO 2 with carbonaceous conductive additives such as amorphous carbon, 12,[27][28][29][30][31][32][33] carbon nanotubes (CNT), 34 graphite oxide 35 and graphene. 25,26,[36][37][38][39] Amongst these carbon materials, graphene is highly attractive as it offers large specic surface area and high electron mobility, which greatly improve lithium ion diffusion kinetics.…”
Section: Introductionmentioning
confidence: 99%